Sea Ice Outlook 2008-2023, Pan-arctic region ... - Hamilton, Lawrence; Bhatt, Uma; Blanchard-Wrigglesworth, Edward; Bushuk, Mitchell; Stroeve, Julienne; Turner-Bogren, Betsy; Wiggins, Helen (NSF Arctic Data Center, 2023)
### Access Dataset and extensive metadata can be accessed and downloaded from the 'Hamilton' directory via: [http://arcticdata.io/data/10.18739/A2WS8HN79](http://arcticdata.io/data/10.18739/A2WS8HN79) ### Overview Each summer since 2008, predictions of September sea ice extent have been solicited from the Arctic research community. This Sea Ice Outlook (SIO) initiative started under the Study of Environmental Arctic Change (SEARCH), with support from the US National Science Foundation and other sources. It grew in subsequent years through two stages of the Sea Ice Prediction Network (SIPN and SIPN2), with results hosted by the Arctic Research Consortium of the United States (ARCUS). Individual and team contributors (including a handful from the general public) employed a variety of dynamical and statistical modeling approaches as well as heuristic methods to make their predictions. From 2008 to 2023 the SIO received over 1,300 pan-Arctic predictions, mostly in waves from early June, July and August. A ...